2014
DOI: 10.7860/jcdr/2014/8339.4554
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intrusion Effects on Maxillary Incisors Among Mini Implant Anchorage, J-Hook Headgear and Utility Arch

Abstract: Background: Intrusion of maxillary incisors is one of the most important and difficult tooth movements to achieve as a part of orthodontic therapy. A variety of techniques were used in the past to intrude the maxillary incisors before the emergence of mini implants in Orthodontics. Mini implants are temporary anchorage devices used to produce various tooth movements. The research was carried out to evaluate and compare the efficiency of producing intrusion of maxillary incisors using mini implants, utility arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 8 publications
1
64
0
4
Order By: Relevance
“…Less extrusive molar movement was noted in the miniscrew group (SMD, À0.86; 95% CI, À1.46 to À0.27; 95% PrI, À3.2 to 1.5; I 2 , 68%; tau 2 , 0.61; 6 RCTs; Figure 4). In one small RCT, 19 the amount of extrusion of the maxillary molars was not statistically significant between the J-HG group and the miniscrew group, with a mean difference of 0.2 mm (P ¼ .5).…”
Section: Results Of Individual Studies and Data Synthesismentioning
confidence: 93%
See 3 more Smart Citations
“…Less extrusive molar movement was noted in the miniscrew group (SMD, À0.86; 95% CI, À1.46 to À0.27; 95% PrI, À3.2 to 1.5; I 2 , 68%; tau 2 , 0.61; 6 RCTs; Figure 4). In one small RCT, 19 the amount of extrusion of the maxillary molars was not statistically significant between the J-HG group and the miniscrew group, with a mean difference of 0.2 mm (P ¼ .5).…”
Section: Results Of Individual Studies and Data Synthesismentioning
confidence: 93%
“…A statistically significant SMD was noted favoring a higher amount of deep-bite reduction in the miniscrew group when compared with the intrusion arch group (SMD, À0.48; 95% CI, À0.89 to À0.07; 95% PrI, À1.45 to 0.49; I 2 , 24%; tau 2 , 0.05; 5 RCTs; Figure 2). One small study 19 compared the amount of deepbite correction between the miniscrews and J-HG. A statistically significant mean difference of À1.5 mm (P ¼ .025) was deduced favoring improved reduction in the deep bite for the miniscrew group.…”
Section: Results Of Individual Studies and Data Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The appliances for incisor intrusion include utility arch by Ricketts, Burstone intrusion arch, Connecticut intrusion arch, and J-hook headgear. 4 Also, recently, many authors have demonstrated the use of mini implants and have reported statistically significant amounts of incisor intrusion with them. 4, , , , Despite the advantages and quick improvements with these treatment options, disadvantages prevail.…”
Section: Introductionmentioning
confidence: 99%